Real-Time Optimization - Dominique Bonvin (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
Process optimization is the method of choice for improving the performance of industrial processes, while enforcing the satisfaction of safety and quality constraints. Long considered as an appealing tool but only applicable to academic problems, optimization has now become a viable technology. Real-time optimization integrates process measurements into the optimization framework. This way, process optimization does not rely exclusively on a (possibly inaccurate) process model but also on process information stemming from measurements. This Special Issue on Real-Time Optimization includes both methodological and practical contributions. All seven methodological contributions deal with explicit schemes that repeat the optimization when new measurements become available. The methods covered include modifier adaptation, economic MPC and the two-step approach of parameter identification and numerical optimization. The six contributions that deal with applications cover various fields including refineries, well networks, combustion and membrane filtration.